What Are the Risk Factors for Infection After Operative Treatment of Peritalar Fracture Dislocations?. Issue 5 (May 2022) - Levitt, Eli B.; Patch, David A.; Johnson, Michael D.; McLynn, Ryan; Debell, Henry; Harris, James B.; Spitler, Clay A.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To assess the risk factors associated with deep infection after operative treatment of peritalar fracture dislocations. Design: A retrospective study was performed to identify patients who had operative treatment of a peritalar fracture dislocation over an 11-year period (2008–2019). Setting: Level 1 trauma center. Participants: Patients were identified by review of all surgical billing that included open reduction of peritalar dislocation. Minimum follow-up for inclusion was 3 months or the outcome of interest. A total of 178 patients were identified, and 154 patients met inclusion criteria. Main Outcome: The primary outcome was deep infection, defined as return to the operating room for debridement with positive cultures. Results: A total of 19 (12.3%) patients developed a postoperative deep infection. The most common associated fractures were talus (47%), calcaneus (33%), and fibula (9%) fractures. The infected group was significantly older (47.2 vs. 39.5 years, P = 0.03). Patients undergoing operative management for peritalar fracture dislocations with current smoking were found to have significantly higher odds of postoperative deep infection (74 vs. 34%, adjusted odds ratio = 7.4, 95% confidence interval, 2.3–24.1, P = 0.001). There was a significantly higher risk of infection in patients with a Gustilo–Anderson type 3 open fracture (32 vs. 12%, adjusted odds ratio = 5.7, 95% confidence interval, 1.6–20.3, P = 0.007). The infected group had high rates of below knee amputation when compared with the group without infection (47 vs. 1%, P < 0.001). Conclusion: In our retrospective study, risk factors for infection after peritalar fracture dislocation included older age, smoking, and Gustilo–Anderson type 3 open fracture. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.